Modulation of Macrophage Responses by CMX, a Fusion Protein Composed of Ag85c, MPT51, and HspX from Mycobacterium tuberculosis - da Costa, Adeliane C.; de Resende, Danilo P.; Santos, Bruno de P. O.; Zoccal, Karina F.; Faccioli, Lúcia H.; Kipnis, André; Junqueira-Kipnis, Ana P. (Frontiers in Microbiology, 2017)
Mycobacterium bovis Bacillus Calmette–Guérin (BCG) is a vaccine used to prevent tuberculosis (TB). Due to the poor protection conferred by BCG in adults, new, more effective formulations have been developed. A recombinant BCG vaccine expressing the CMX fusion protein Ag85c_MPT51_HspX (rBCG-CMX) induced Th1 and Th17 responses and provided better protection than BCG. It has been shown that Mycobacterium smegmatis expressing CMX also induces better protection than BCG and is a strong macrophage activator. The aim of the present study was to evaluate macrophage activation by the recombinant CMX fusion protein and by rBCG-CMX and to evaluate their ability to generate vaccine-specific immune responses. The results demonstrate that rCMX protein expressed by BCG (rBCG-CMX) activates pulmonary macrophages; increases the expression of activation molecules, cytokines, and MHC-II. The interaction with rCMX activates the transcription factor NF-κB and induces the production of the cytokines TGF-β, TNF-α, and IL-6. The in vitro stimulation of bone marrow-derived macrophages (BMMs) from TLR-4 or TLR-2 KO mice showed that in the absence of TLR-4, IL-6 was not produced. rBCG-CMX was unable to induce CMX-specific Th1 and Th17 cells in TLR-4 and TLR-2 KO mice, suggesting that these receptors participate in their induction. We concluded that both the rBCG-CMX vaccine and the rCMX protein can activate macrophages and favor the specific immune response necessary for this vaccine.